KEDUDUKAN KETETAPAN MPR BERDASARKAN UU NO. 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Delfina Gusman; Andi Nova (Jurnal Dinamika Hukum, 2012)
MPR Decree in resettlement of legislation under the Constitution of 1945 on the basis of Law No. 12 Year 2011 cocerning formation of legislation gives rise to a variety of polemics in the position of the MPR as State institutions. Provisions of the MPR is considered to have urgency in Indonesia's system, because the MPR as State institutions is considered to still have the duty and the authority of its strategic, e.g: inauguration of President and Vice President, the establishment of the Constitution. MPR also made provisions as one of basic national legislation program. Keywords : MPR Decree, national legislation program, rule of law